2019
DOI: 10.1177/0170840619847724
|View full text |Cite
|
Sign up to set email alerts
|

The Enduring State: An analysis of governance-making in three mining conflicts

Abstract: This article investigates the profound ambiguity of the state in the organization of contemporary business–society relations. On the one hand, there has been a decisive shift from government to governance, encouraging private actors, such as corporations, communities and NGOs, to address social and environmental concerns themselves, i.e. without the state’s involvement. On the other hand, however, the continued importance and relevance of the organized state is difficult to ignore. In this article we examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 78 publications
0
19
0
1
Order By: Relevance
“…The articles cover topics as diverse as international standardization, corporate (ir)responsibility, community relations, and even the license to exist of particular industries. In terms of theoretical grounding, the contributions are equally diverse, ranging for instance from Foucauldian governmentality in the context of the Chilean mining industry (Maher et al, 2019), to transnational institutionalism and regulation theory (Boghossian & Marques, 2019), and an in-depth conceptual analysis of political science theories (Eberlein, 2019). Methodologically, two conceptual studies (Eberlein, 2019;Schneider & Scherer, 2019) are complemented by four qualitative studies, some of the latter drawing on a longitudinal research design to explore how government-business dynamics evolve over time (Alon et al, 2019;Hamann, 2019).…”
Section: Problematizing the Governance Of Business Conduct: The Contrmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles cover topics as diverse as international standardization, corporate (ir)responsibility, community relations, and even the license to exist of particular industries. In terms of theoretical grounding, the contributions are equally diverse, ranging for instance from Foucauldian governmentality in the context of the Chilean mining industry (Maher et al, 2019), to transnational institutionalism and regulation theory (Boghossian & Marques, 2019), and an in-depth conceptual analysis of political science theories (Eberlein, 2019). Methodologically, two conceptual studies (Eberlein, 2019;Schneider & Scherer, 2019) are complemented by four qualitative studies, some of the latter drawing on a longitudinal research design to explore how government-business dynamics evolve over time (Alon et al, 2019;Hamann, 2019).…”
Section: Problematizing the Governance Of Business Conduct: The Contrmentioning
confidence: 99%
“…In their exploration of mining conflicts in Chilean local communities, Maher, Valenzuela and Böhm (2019) argue that the state is simultaneously seemingly materially absent while still having a strong influence on local outcomes. The study presents a hybrid theory combining elements of central steering and dispersed vouching.…”
Section: Problematizing the Governance Of Business Conduct: The Contrmentioning
confidence: 99%
“…The local mobilization appears even more significant because of the extreme environmental conditions in which it is taking place and the unlikely capacity of the residents to stop the largest gold mining company in the world (Li, 2017). The paradigmatic nature of this dispute has attracted, from the very beginning, a vast echo, including some academic interest (Arboleda, 2015;Cavallo;, Li, 2017Maher, Valenzuela, & Böhm, 2019;Smith & McCormick, 2019;Urkidi & Walter, 2011). While our study builds on previous analyses, it aims to deploy a more comprehensive socio-legal explanatory framework of material and symbolic struggles, focusing on the community's rights mobilization.…”
Section: Case Selection and Research Contextmentioning
confidence: 99%
“…Environmental and social damage caused by mining tends to increase opposition to projects from the sector. Corporate Social Responsibility (CSR) is often used to mitigate this opposition and prevent clashes with communities affected by mining (Banerjee, 2014;Maher, Valenzuela & Böhm, 2019). Research has already shown that CSR practices change when applied in developing countries (Jamali, et al, 2017).…”
Section: Practical Implications 1 Introductionmentioning
confidence: 99%